Is the Public Good Role of Higher Education Under Attack? - Hazelkorn, Ellen (International Higher Education, 2017)
Higher education has long argued that it is a public good because of its contribution to societal goals. These assumptions are coming under growing public scrutiny as universities seek to pursue their own agenda, at home and increasingly internationally. This article looks at some of the issues.